Changing Parental Style for the Management of Childhood Obesity: A Multi-Component Group Experience - Idelson, Paola Iaccarino; Zito, Eugenio; Mozzillo, Enza; Lista, Mary; Mobilia, Sara; Valerio, Giuliana; Franzese, Adriana (International Journal of Child Health and Nutrition, 2015)
Obesity is a complex public health issue with increasing prevalence in childhood and with a large burden on physical and mental health. Recent data suggest the effectiveness of multi-component approach, of interventions aimed at changing parenting style, and of group educational sessions. In particular, interventions containing a family-behavioral component produce larger effect sizes than alternative treatment groups. Many models have been developed for the multi-component and multi-stakeholder treatment of childhood obesity, with a frequent discrepancy in the intensity of the treatment programme and in the resources available within clinics. Looking for effective strategies for the treatment of childhood obesity we built a Multi-component Obesity Group Experience (MOGE) model, analysing BMI and fat mass reduction as primary outcomes and qualitative improvements in the behavior towards nutrition and lifestyle as secondary one. Thirty-five consecutive obese children (20 girls, BMI z-score 2.1+0.2), were treated by MOGE model and the results were compared with 35 matched obese subjects of the same age (control group followed with a traditional treatment). After 3, 6 and 12 months of treatment it has been observed a significant reduction of BMI z-score and body fat mass. Moreover, a clinically significant psychological wellness was observed in children of MOGE group.